Are CAR-T therapies living up to their hype? A study using real-world data in two cohorts to determine how well they are actually working in practice compared with bone marrow transplants. Issue 3 (17th July 2019) - Schulthess, Duane; Gassull, Daniel; Makady, Amr; Ludlow, Anna; Rothman, Brian; Have, Pieter ten; Wu, Yiyang; Ekstrom, Leeland; Minnema, Monique; Jagasia, Madan
Abstract : With the increasing use of new regulatory tools, like the Food and Drug Administration's breakthrough designation, there are increasing challenges for European health technology assessors (HTAs) to make an accurate assessment of the long-term value and performance of chimeric antigen receptor T-cell (CAR-T) therapies, particularly for orphan conditions, such as acute lymphoblastic leukaemia. The aim of this study was to demonstrate a novel methodology harnessing longitudinal real-world data, extracted from the electronic health records of a medical centre functioning as a clinical trial site, to develop an accurate analysis of the performance of CAR-T compared with the next-best treatment option, namely allogeneic haematopoietic cell transplant (HCT). The study population comprised 43 subjects in two cohorts: 29 who had undergone HCT treatment and 14 who had undergone CAR-T therapy. The 3-year relapse-free survival probability was 46% (95% CI: 08% to 79%) in the CAR-T cohort and 68% (95% CI: 46% to 83%) in the HCT cohort. To explain the lower RFS probability in the CAR-T cohort compared with the HCT cohort, the authors hypothesised that the CAR-T cohort had a far higher level of disease burden. This was validated by log-rank test analysis (p=0.0001) and confirmed in conversations with practitioners at the study site. The authors are aware that the small populations in this study will be seen as limiting the generalisability of the findings to some readers. However, in consultation with many European HTAs and regulators, there is broad agreement that this methodology warrants further investigation with a larger study.